2001
DOI: 10.1046/j.1365-2222.2001.01107.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo airway eosinophil accumulation induced by polymyxin‐B reduces bronchial responsiveness in guinea pigs

Abstract: These results suggest that in vivo airway eosinophils may reduce non-specific bronchial responsiveness through inhibitory or bronchoprotective prostanoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Ishiura et al reported that in vivo airway eosinophils accumulation did not worsen asthma physiology, i.e. bronchial responsiveness and allergic bronchoconstriction, in guinea pigs (15). Therefore, we speculate that eosinophil may not play a key role in the development of CS-AEP.…”
Section: Discussionmentioning
confidence: 63%
“…Ishiura et al reported that in vivo airway eosinophils accumulation did not worsen asthma physiology, i.e. bronchial responsiveness and allergic bronchoconstriction, in guinea pigs (15). Therefore, we speculate that eosinophil may not play a key role in the development of CS-AEP.…”
Section: Discussionmentioning
confidence: 63%
“…Most of the experience using aerosolized polymyxins is with colistin and is likely due to the fact that polymyxin B can lead more frequently than colistimethate sodium to release of histamine during nebulization and thus, bronchoconstriction. 38,39 …”
Section: Inhaled Polymyxins In Critically Ill Patientsmentioning
confidence: 99%
“…However, these associations with eosinophils are not proof of causation, and recent studies have questioned the role of the eosinophil as a harmful cell [49–52], and even suggested that eosinophils can act as bystanders [53] or part of complex cell interactions and repair mechanisms [24,35,54]. Recruitment of eosinophils is linked with Th2 immune responses [54–56], since eosinophil production and recruitment appear to be mediated by the Th2 cytokines IL‐5, IL‐4 and IL‐13 [57,58].…”
Section: The Eosinophil Hypothesismentioning
confidence: 99%